Economic impacts of overweight and obesity: current and future estimates for 161 countries. Issue 9 (20th September 2022) - Okunogbe, Adeyemi; Nugent, Rachel; Spencer, Garrison; Powis, Jaynaide; Ralston, Johanna; Wilding, John
Abstract : Introduction: The scope of the challenge of overweight and obesity (OAO) has not been fully realised globally, in part because much of what is known about the economic impacts of OAO come from high-income countries (HICs) and are not readily comparable due to methodological differences. Our objective is to estimate the current and future national economic impacts of OAO globally. Methods: We estimated economic impacts of OAO for 161 countries using a cost-of-illness approach. Direct and indirect costs of OAO between 2019 and 2060 were estimated from a societal perspective. We assessed the effect of two hypothetical scenarios of OAO prevalence projections. Country-specific data were sourced from published studies and global databases. Results: The economic impact of OAO in 2019 is estimated at 2.19% of global gross domestic product (GDP) ranging on average from US$20 per capita in Africa to US$872 per capita in the Americas and from US$6 in low-income countries to US$1110 in HICs. If current trends continue, by 2060, the economic impacts from OAO are projected to rise to 3.29% of GDP globally. The biggest increase will be concentrated in lower resource countries with total economic costs increasing by fourfold between 2019 and 2060 in HICs, whereas they increase 12–25 times in low and middle-income countries. Reducing projected OAO prevalence by 5% annually from current trends or keeping it at 2019 levels will translate into average annual reductions of US$429 billion or US$2201 billion in costs, respectively, between 2020 and 2060 globally. Conclusion: This study provides novel evidence on the economic impact of OAO across different economic and geographic contexts. Our findings highlight the need for concerted and holistic action to address the global rise in OAO prevalence, to avert the significant risks of inaction and achieve the promise of whole-of-society gains in population well-being.